KEGIATAN KOMUNIKASI PEMASARAN ENGLISH FIRST SOLO - Nurnawati Hindra H, Mayrizky Ramadhani, Bedjo Sukarno & (Transformasi, 2016)
Without realizing there are many changes that occur in this country as fast growingglobalization. As we know, most tools and technologies today are in English. Seeing theseconditions, emerge many of English course in Indonesia and Solo in particular are competing tooffer services that aims to help people improve the competence and ability of their English skill.The purpose of this research is to describe and learn about the Marketing Communication atEnglish First Solo. In accordance with the theory presented by Phillip Kotler and Kevin LaneKeller that marketing communication is a social process in which individuals and groups obtainwhat they need and want by creating, offering, and freely exchanging products of value withother products. Data collection techniques in this research through interviews, observation andliterature data. Data analysis technique used in this research is data reduction, datapresentation, and conclusion. The results showed that marketing communication activitiesconducted by English First Solo is through advertising, personal selling, publicity, and salespromotion.Key word: Marketing Communication